Performance evaluation of EKF-SLAM algorithm using an ASC in marine environments - Si, Jian Wen. (2012)
This report examines how different sensor data captured can be fused to the Simultaneous Localization and Mapping (SLAM) algorithm to improve the navigation of the Autonomous Surface Craft. It will first look into the on-board system and the different sensors used to capture the data. Following which, it will also look into the process and techniques used for data extraction. Feature extraction plays an important part in map building and improving the accuracy of the SLAM algorithm and will be discussed in detail. Concepts and usage of the SLAM algorithm will play a major role in finding ways to fuse the sensor data and improving the algorithm.